Data Mining Classification to Predict Student Graduation Using the Naive Bayes Method - jefri, jefri; Fatah, Zaehol (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 5 No 3 (2024): JITTER, Vol.5, No.3, December 2024DO - 10.24843/JTRTI.2024.v05.i03.p07, 2025)
Data mining helps provide precise and careful decisions. Student graduation on time is one of the assessment points in the higher education accreditation process. However, student graduation cannot always be detected quickly, which can reduce the assessment of a university in the accreditation process. This problem arises to find out whether students will be able to graduate on time or not. Classification method for predicting student graduates using the Naïve Bayes algorithm. Whether a student graduates on time or not, it is hoped that the results will provide information and input for the university in making future policies. From the results of this test, it was found that by applying the Naïve Bayes algorithm the system can predict student graduation in a timely manner. After comparing several literatures, it can be concluded that this method can be used for this prediction with an accuracy rate of 90%. This literature review is important as a supporting factor for research.